Successional soil acidification links bacterial community shifts to nitrogen-cycling gene potential in a subalpine spruce chronosequence - Hangyu Bai; Bingjin Wang; Xiuling Yang; Shunzhi Xue; Wenyuan Li; Caishun Qi; Kun Ma; Dengwu Li (Applied Soil Ecology, 2026)

Identification of the SlRCC1 gene family and characterization of SlRCC1-13 in cold stress response in tomato (Solanum lycopersicum) - Huixin Zhang; Xueyao Zeng; Yixiao Bai; Yuxin Liu; Rui LV; Fulei Mo; Mingfang Feng; Shusen Liu; Xiuling Chen; Aoxue Wang (Plant Science, 2026)

Coordination chemistry-guided construction of hierarchical lignin-derived porous carbon with dual Lewis acid–base sites for synergistic CO2 capture - Xinxin Niu; Li Bai; Xiuling Xu; Fujun Wang; Shuai Zhu; Yixian Xue; Zhi Liu; Zhao Chen (Chemical Engineering Journal, 2026)

Temperature-dependent effects of lanthanum-modified bentonite on sediment nitrogen removal processes and the underlying microbial mechanisms - Penglong Wang; Jiehua Wang; Pingping Zhang; Zhiqiang Jiao; Xiuling Bai; Zhonghua Zhao; Jinyue Fan; Songwei Zhang; Bing Zhao; Xiubo Ren; Huidian Dou; Wenhao Bai (Water Research, 2026)

Rhizosphere microbial diversity and community assembly in tree species–slope aspect coupled mountain forests of the Qilian Mountains, northeastern Qinghai–Tibet Plateau - Hangyu Bai; Qian Chen; Xiuling Yang; Dengwu Li (Applied Soil Ecology, 2026)

Effects of human disturbance on the landscape pattern in the mountainous area of western Henan, China - Haoran Wang; Kaiyue Wang; Yunkai Zhou; Xiuling Bai (Journal of Environmental Management, 2025)

Analysis of population structure and genetic diversity of Camellia tachangensis in Guizhou based on SNP markers - Dejun Huang; Suzhen Niu; Dingchen Bai; Zhifei Zhao; Caiyun Li; Xiuling Deng; Yihan Wang (Molecular Biology Reports, 2024)
Background Camellia tachangensis F. C. Zhang is a five-compartment species in the ovary of tea group plants, which represents the original germline of early differentiation of some tea group plants. Methods and results In this study, we analyzed single-nucleotide polymorphisms (SNPs) at the genome level, constructed a phylogenetic tree, analyzed the genetic diversity, and further investigated the population structure of 100 C. tachangensis accessions using the genotyping-by-sequencing (GBS) method. A total of 91,959 high-quality SNPs were obtained. Population structure analysis showed that the 100 C. tachangensis accessions clustered into three groups: YQ-1 (Village Group), YQ-2 (Forest Group) and YQ-3 (Transition Group), which was further consistent with the results of phylogenetic analysis and principal component analyses (PCA). In addition, a comparative analysis of the genetic diversity among the three populations (Forest, Village, and Transition Groups) detected the highest genetic diversity in the Transition Group and the highest differentiation between Forest and Village Groups. Conclusions C. tachangensis plants growing in the forest had different genetic backgrounds from those growing in villages. This study provides a basis for the effective protection and utilization of C. tachangensis populations and lays a foundation for future C. tachangensis breeding.

Variations of sediment organic phosphorus and organic carbon during the outbreak and decline of algal blooms in Lake Taihu, China - Jiehua Wang; Xiuling Bai; Wenchao Li; Pingping Zhang; Mengdi Zhang; Haoran Wang; Yingge Bai (Journal of Environmental Sciences, 2024)

Study on metal elements in indoor particulate matter: a case study of rural residential environment in Northeast China - Chunhui Li; Li Bai; Jia Qin; Yuqi Guo; Han Wang; Xiuling Xu (Environmental Geochemistry and Health, 2023)

Pollution characteristics and health hazards of PAHs in PM1.0 in the cooking environment - Jinpeng Si; Li Bai; Xiuling Xu; Chunhui Li (Building and Environment, 2023)

Effects of heavy rain on the concentrations and forms of carbon, nitrogen and phosphorus in urban rivers of northern China - Wenchao Li; Jiehua Wang; Yunkai Zhou; Pingping Zhang; Xiuling Bai (Environmental Science and Pollution Research, 2023)

Comparison between diffusive gradients in thin film technology (DGT) and traditional methods for prediction of plant available heavy metals in agricultural soil - Xiuling Bai; Wenna Ye; Yunkai Zhou; Xinling Ruan; Jiehua Wang; Wenchao Li; Pingping Zhang (Journal of Soils and Sediments, 2023)

The Improving of Cd2+ Adsorption Performance of Hydrochar Obtained from Corn Straw Waste with KOH Activation - Yan Shi; Heng Li; Yushi Rong; Li Bai; Mingshu Chi; Xiuling Xu; Chenglin Li; Hao Bai; Yue Liu (Water, Air, & Soil Pollution, 2022)

Effects of polystyrene microplastics on copper toxicity to the protozoan Euglena gracilis: emphasis on different evaluation methods, photosynthesis, and metal accumulation - Xiuling Li; Zhengjun Wang; Ming Bai; Zhehua Chen; Gan Gu; Xi Li; Changwei Hu; Xuezhen Zhang (Environmental Science and Pollution Research, 2022)

Modification of microcrystalline cellulose with acrylamide under microwave irradiation and its application as flocculant - Xiuling Yu; Xuejiao Huang; Changzhuang Bai; Xiaopeng Xiong (Environmental Science and Pollution Research, 2019)